Achieving High-Resolution Hard X-ray Microscopy using Monolithic 2D Multilayer Laue Lenses. (November 2022) - Xu, Wei; Xu, Weihe; Bouet, Nathalie; Zhou, Juan; Yan, Hanfei; Huang, Xiaojing; Lu, Ming; Zalalutdinov, Maxim; Chu, Yong S.; Nazaretski, Evgeny
Abstract : Abstract: This article introduces the 2D multilayer Laue lens (MLL) nanofocusing optics recently developed for high-resolution hard X-ray microscopy. The new optics utilized a micro-electro-mechanical-system (MEMS)-based template to accommodate two linear MLL optics in a pre-aligned configuration. Angular misalignment between the two lenses was controlled in tens of millidegrees, and the lateral position error was on a micrometer scale. Using the developed 2D MLLs, an astigmatism-free point focus of approximately 14 nm by 13 nm in horizontal and vertical directions, respectively, at 13.6 keV photon energy was obtained. The success of 2D MLL optics with an approaching 10 nm resolution is a significant step forward for the development of high-resolution hard X-ray microscopy and applications of MLL optics in the hard X-ray community.